Analisis Keputusan Pembelian Kebutuhan Pokok Mie Instan Ditinjau dari Maqashid Syariah - lifia, lifia; Masriyah, Siti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In carrying out modern human life, it continues to experience quite significant changes and demands speed and dynamics in an action including consumption activities, this is also experienced by students. Which describes their life, until they finally make a purchasing decision to meet their basic needs, instant noodles are the alternative they have chosen. Instant noodle producers keep popping up with various price promotions, flavor variants and even halal labeling. Consuming instant noodles is a culture that has long and commonly been applied to society, but in that process have you prioritized self-care in order to obtain life's welfare as promised by maqasid Syariah which is the rules for living life by Muslims. Using a qualitative method with a case study approach and techniques purposive sampling.